Religious tourism in municipalities in the state of Amazonas - Maria Adriana S. B. Teixeira; Lúcia Cláudia Barbosa Santos; Maria Jacqueline Ramos Iwata; Anny Gabrielly Peixoto de Oliveira (Via@)
This study deals with the main religious aspects of three major events that propagate religious tourism in the state of Amazonas. Religious tourism is driven by the religious particularities of each tourist, who seek places considered sacred and recognized for their acts of faith, as well as for the graces achieved. The general objective of the study is to analyze the main characteristics of the religious tourism of Nossa Senhora do Carmo (Parintins); The feast of Santo Antônio de Borba (Borba) and Nossa Rainha do Rosário (Itapiranga). The results showed that the main characteristics of the studied events are to keep the religious traditions passed down from generations, to strengthen the devotion to the local patron saint and to